Dissatisfaction and profile of dissatisfied consumers: a case study of mobile telecommunication network consumers in Nigeria - Chinedu, Anyanwu Hilary; Haron, Sharifah Azizah; Osman, Syuhaily; Hayatu, Hilary Faith (Canadian Center of Science and Education, 2020)
This research paper examined the dissatisfaction of Mobile telecommunication network (MTN) consumers in Nigeria. The researchers used expectancy disconfirmation theory (EDT) to argue that with high and prolonged consumer dissatisfaction, educated MTN consumers are prone to exit their service chain for other telecom companies. Contrary to MTN’s promises upon entry into the Nigerian telecom market, its consumers have been groaning against substandard services offered to them by MTN. Adequate supply, stability, and maintenance/hitch free services lead to consumer satisfaction, while deficiency of the stated factors aggravates consumers, thus consumer dissatisfaction. This quantitative research utilized a cross-sectional design and adopted a stratified sampling technique to incorporate 385 MTN consumers in Lagos, Nigeria. IBM SPSS version 22 was used for the data analysis. The data set consisted of 58.2% males and 41.8% females. Descriptive statistics found that 43.9% of MTN consumers were highly dissatisfied while 56.1% were lowly dissatisfied. A Chi-square test revealed that only educational level is significantly associated with dissatisfaction among the six selected background variables. Also, logistic regression showed age, educational level, and religion as significant predictors of high dissatisfaction among consumers. Educated consumers tend to sensitize service outcomes more than uneducated ones as a result of their wealth of information. Older (aged) and religious consumers will also evaluate marketing episode critically more than younger and non-religious ones. Results further imply that consumers’ educational level is a catalyst of expectancy disconfirmation theory in service sectors. MTN or similar commercial enterprises should focus on the causes of dissatisfaction and strategize on how to ameliorate the dissatisfaction level among their consumers. Firms should embark on promotional offers and other stimuli activities to regain their consumers’ trust and loyalty; hence, it will extend their market share and dominance.